Restoration of the Orbital Aesthetic Subunit with the Thoracodorsal Artery System of Flaps in Patients Undergoing Radiation Therapy - Chanowski, Eric J.P.; Casper, Keith A.; Eisbruch, Avraham; Heth, Jason A.; Marentette, Lawrence J.; Prince, Mark E.; Moyer, Jeffrey S.; Chepeha, Douglas B. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objectives To demonstrate the advantages of the thoracodorsal artery scapular tip autogenous transplant (Tdast) for patients requiring restoration of the orbital aesthetic subunit.Design Prospective case series.Setting Tertiary center.Participants Ten patients (M:F,6:4) with a mean age of 56 years (range, 21 to 78 years) underwent restoration of the orbital aesthetic subunit and radiation therapy between 2001 and 2008.Main Outcome Measures The two reconstructive advantages of the thoracodorsal artery system of flaps for orbital reconstruction are a long pedicle and the suitability of the scapula tip to meet the three-dimensional requirements of the orbit. Patients were assessed 1 year or more after treatment for cosmetic outcome, work status, and socialization.Results Eight of 10 patients benefited from the three-dimensional nature of the scapula tip bone and 7 of 10 avoided vein grafting. Four of five evaluable patients reported “frequently” socializing outside their home. Four of five evaluable patients working before undergoing their treatment were able to return to work posttreatment. Seven of nine patients with postoperative photographs had minimal or no facial contour deformity.Conclusions The Tdast can restore orbital contour without osteotomy, and the thoracodorsal artery system of flaps has a long vascular pedicle that reduces vein grafting. Patients have an acceptable cosmetic result and return to preoperative work status and socialization.
Keywords: thoracodorsal artery scapular tip autogenous transplant; Tdast; scapula; orbit; orbital evisceration